Neuroprotective Effects of a Traditional Multi-Herbal Medicine Kyung-Ok-Ko in an Animal Model of Parkinson's Disease: Inhibition of MAPKs and NF-κB Pathways and Activation of Keap1-Nrf2 Pathway - Choi, Jong Hee; Jang, Minhee; Lee, Joon-Il; Chung, Won-Seok; Cho, Ik-Hyun (Frontiers in Pharmacology, 2018)
Kyung-Ok-Ko (KOK), a traditional multi-herbal medicine, has been widely used in Oriental medicine as a restorative that can enforce vitality of whole organs and as a medicine that can treat age-related symptoms including lack of vigor and weakened immunity. However, the beneficial effect of KOK on neurological diseases such as Parkinson’s diseases (PD) is largely unknown. Thus, the objective of this study was to examine the protective effect of KOK on neurotoxicity in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of PD. Pre-treatment with KOK at 1 or 2 g/kg/day (p.o.) showed significant mitigating effects on neurological dysfunction (motor and welfare) based on pole, rotarod, and nest building tests. It also showed effects on survival rate. These positive effects of KOK were related to inhibition of loss of tyrosine hydroxylase–positive neurons, reduction of MitoSOX activity, increased apoptotic cells, microglia activation, and upregulation of inflammatory factors [interleukin (IL)-1β, IL-6, cyclooxygenase-2, and inducible nitric oxide], and reduced blood-brain barrier (BBB) disruption in the substantia nigra pars compacta (SNpc) and/or striatum after MPTP intoxication. Interestingly, these effects of KOK against MPTP neurotoxicity were associated with inhibition of phosphorylation of mitogen-activated protein kinases and nuclear factor-kappa B signaling pathways along with up-regulation of nuclear factor erythroid 2-related factor 2 pathways in SNpc and/or striatum. Collectively, our findings suggest that KOK might be able to mitigate neurotoxicity in MPTP-induced mouse model of PD via multi-effects, including anti-neuronal and anti-BBB disruption activities through its anti-inflammatory and anti-oxidative activities. Therefore, KOK might have potential for preventing and/or treating PD.